PELONTAR SHUTTLECOCK MODIFIKASI SEBAGAI ALTERNATIF LATIHAN BULUTANGKIS YANG EFISIEN DAN TERJANGKAU - Rivan Saghita Pratama; Indra Ramadhan; Salma Nabila Putri; Bakhirotun Nikmah (STKIP Subang, 2025)
Technological developments in the world of sports have brought significantchanges in the training methods and skills development of athletes, including inbadminton which requires intensive and structured training to achieve optimalperformance. This study aims to examine the development of a modifiedshuttlecock launcher as an alternative technology to support badminton trainingthat is efficient and affordable for various sports participants. As a sportstechnology innovation, the modified shuttlecock launcher is designed to meet theneeds of independent training, improve consistency, and provide a moremeasurable and systematic variation of training programs. The research methoduses a research and development approach with a focus on modifying mechanicaland electronic components to create an affordable tool that still performsadequately for training needs. The results showed that the modified shuttlecocklauncher was able to increase training efficiency in terms of time, energy, and costcompared to conventional methods or the use of commercial tools, as well asproviding significant benefits in increasing the consistency of strokes and theaccuracy of players technical skills. This study concludes that the development ofmodified shuttlecock launching technology is an innovative solution that bridgesthe gap in technology accessibility in badminton, providing an efficient andaffordable alternative for athletes, coaches, and sports institutions with limitedresources. The implications of this research provide a basis for the furtherdevelopment of adaptive and inclusive sports technology, as well as encouragingan ecosystem of innovation in improving the quality of badminton training inIndonesia and the world.